Who's buying groceries. (Who's buying series., 2018)
The 13th edition of Who's Buying Groceries is based on unpublished data collected by the Bureau of Labor Statistics' 2014 Consumer Expenditure Survey. It examines how much Americans spend on food at grocery and convenience stores by the demographics that count: age, income, high-income households, household type, race and Hispanic origin, region of residence, and education. To round out the spending picture, it also presents who-are-the-best-customers analyses of the data, showing the demographics of the best and biggest customers at a glance. The 80-plus items examined in this report range from bacon to coffee, cereal, and the supermarket deli. The individual products fall within the categories of cereals and bakery products; meats, poultry, fish, and eggs; dairy products; fruits and vegetables; sugar and other sweets; fats and oils; and a miscellaneous category that includes fresh prepared food, snacks, condiments and seasonings, and nonalcoholic beverages. Also in this edition is a unique analysis of spending since the Great Recession.